Pelatihan Menulis Karangan Narasi Dengan Penggunaan Media Bergambar Siswa SDN 1 Negeri Agung Tanggamus - Muhammad Singgih; Tri Maya Sari; Eny Dwi Marcela; Riska Aprilliya (STIT Darul Fattah Bandar Lampung, 2023)
Writing becomes a productive activity that has a relationship with one's thought process and expression skills. This PKM aims to improve students' ability in terms of writing narrative essays with the use of image media. This service is carried out by pre-implementation, implementation and post-implementation methods. The results of this PKM activity show that fluency in the learning process, thinking process and the process of writing children's narrative essays with the presence of picture media in learning.